PENGELOLAAN KONTEN INSTAGRAM BEAUTY VLOGGER DALAM MEMBANGUN PERSONAL BRANDING - Cahayani, Dita; Femi Oktaviani (Linimasa : Jurnal Ilmu Komunikasi, 2023)
Instagram is one of the social media that is in great demand by the public, various interesting features allow users to use it to create works or become certain professions. There are several types of Instagram content, one of which is beauty vloggers, now it has become a very interesting trend among generation Z because you can find various beauty content to compete in presenting yourself. The beauty here includes the use of makeup, and skincare to fashion with their own characteristics, a beauty vlogger in managing their content. The purpose of this research is to find out how managing Instagram content can build personal branding. Creativity in managing Instagram beauty vlogger content can show the qualities you have to create personal branding. This is very important given the increasingly complex competition that is occurring, one way to show the identity of a beauty vlogger is through personal branding, which is a process to regulate and control other people's perceptions of the personal branding that is built. This study uses qualitative methods with a post-positivism approach. The results found by researchers are that beauty vlogger Sandra has four components in her content planning, namely introductions, problems, solutions, and recommendations. Visualization as the main key in interesting content is characteristic of beauty vloggers and communication barriers in expressing inspiration as something that content creators need to understand. In the development of the times, content creators can advance the delivery of messages that are created, especially in visualization. Keywords: Content management, Beauty vlogger, Personal branding